2014
DOI: 10.4067/s0718-07642014000200015
|View full text |Cite
|
Sign up to set email alerts
|

Oleína De Palma Estabilizada Con Antioxidante Natural De Romero en Un Proceso Discontinuo De Fritura

Abstract: En este estudio se evalúo el contenido de fenoles totales y la actividad antioxidante por diferentes metodologías como: DPPH, FRAP y ORAC de un producto comercial Noxy-Nat® reportado como antioxidante natural de romero. El Noxy-Nat a 1000 ppm inhibió en un 59% el deterioro oxidativo del aceite de palma, sometido a un proceso discontinuo de fritura de pollo a 180°C. El proceso oxidativo fue monitoreado usando el valor de peróxido (VP) y los compuestos polares totales (CPT) como indicadores de la peroxidación li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Recently, several studies have evaluated the effect of the addition of plant derived extracts rich of antioxidant compounds on the oxidative stability of vegetable and animal oils and fats. [ 3,6–8 ] Similar or better stability was reported compared to the commonly used synthetic antioxidants. This tendency is especially outlined at elevated temperatures such as those reached during frying.…”
Section: Introductionmentioning
confidence: 64%
See 1 more Smart Citation
“…Recently, several studies have evaluated the effect of the addition of plant derived extracts rich of antioxidant compounds on the oxidative stability of vegetable and animal oils and fats. [ 3,6–8 ] Similar or better stability was reported compared to the commonly used synthetic antioxidants. This tendency is especially outlined at elevated temperatures such as those reached during frying.…”
Section: Introductionmentioning
confidence: 64%
“…The enthalpy of activation ΔH ‡ and entropy of activation ΔS ‡ were determined using the Eyring equation [7,30]…”
Section: Determination Of Kinetic and Thermodynamic Parameters Of Oximentioning
confidence: 99%
“…Fluorescence was recorded on a Perkin Elmer LS45 spectrofluorometer with a thermostatedmulticell. The ORAC value µmol Trolox/g was calculated by a calibration curve using different concentrations of Trolox ® [16] [20].…”
Section: Oxygen Radical Absorbance Capacity (Orac) Assaymentioning
confidence: 99%
“…Preliminary studies in different rosemary extracts have reported carnosic acid and rosmarinic acid as compounds with high antioxidant activity [13]- [16].…”
Section: Determination Of Carnosic and Rosmarinic Acid Contentmentioning
confidence: 99%
See 1 more Smart Citation